Disentangling molecular and clinical stratification patterns in beta-galactosidase deficiency - ELÇİOĞLU, HURİYE NURSEL (BMJ PUBLISHING GROUP, 2021)
Introduction This study aims to define the phenotypic and molecular spectrum of the two clinical forms of beta-galactosidase (beta-GAL) deficiency, GM1-gangliosidosis and mucopolysaccharidosis IVB (Morquio disease type B, MPSIVB). Methods Clinical and genetic data of 52 probands, 47 patients with GM1-gangliosidosis and 5 patients with MPSIVB were analysed. Results The clinical presentations in patients with GM1-gangliosidosis are consistent with a phenotypic continuum ranging from a severe antenatal form with hydrops fetalis to an adult form with an extrapyramidal syndrome. Molecular studies evidenced 47 variants located throughout the sequence of the GLB1 gene, in all exons except 7, 11 and 12. Eighteen novel variants (15 substitutions and 3 deletions) were identified. Several variants were linked specifically to early-onset GM1-gangliosidosis, late-onset GM1-gangliosidosis or MPSIVB phenotypes. This integrative molecular and clinical stratification suggests a variant-driven patient assignment to a given clinical and severity group. Conclusion This study reports one of the largest series of b-GAL deficiency with an integrative patient stratification combining molecular and clinical features. This work contributes to expand the community knowledge regarding the molecular and clinical landscapes of b-GAL deficiency for a better patient management.
Keywords: brain damage; chronic; brain diseases; metabolic; central nervous system diseases; genomics; MORQUIO B DISEASE; ELASTIN-BINDING PROTEIN; GM1 GANGLIOSIDOSIS; GENE-MUTATIONS; IMPAIRED ELASTOGENESIS; GM1-GANGLIOSIDOSIS; FIBROBLASTS; POLYMORPHISM; EXPRESSION; ADULTS